2020
DOI: 10.1111/ijpo.12625
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial examining an exam room poster to prompt communication about weight

Abstract: Background: Recognition of childhood weight status is important to the adoption of healthy lifestyle behaviours.Objectives: We assessed whether an exam room educational poster addressing weight and healthy lifestyle behaviours was acceptable to parents, prompted parentprovider communication or improved parental weight perception accuracy.Methods: In this multi-site randomized controlled trial, exam rooms were randomized to display the posters (English and Spanish) or not. Children ages 3 to 8 years (N = 965) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A poster also utilizes downtime while parents wait to see their provider. Previous work shows that posters can be successful pediatric public health education tools, ( Brown et al, Jul 2020 , Herrera et al, 2013 ) and may help facilitate conversations about pediatric weight. ( Brown et al, Jul 2020 ) We intend to examine whether our poster improves parent/provider communication about early life obesity prevention in future research.…”
Section: Discussionmentioning
confidence: 99%
“…A poster also utilizes downtime while parents wait to see their provider. Previous work shows that posters can be successful pediatric public health education tools, ( Brown et al, Jul 2020 , Herrera et al, 2013 ) and may help facilitate conversations about pediatric weight. ( Brown et al, Jul 2020 ) We intend to examine whether our poster improves parent/provider communication about early life obesity prevention in future research.…”
Section: Discussionmentioning
confidence: 99%
“…To make the "invisible" nature of excess weight concrete, the healthcare professionals in our study reported that they used growth charts to objectively compare the child's weight status to with a healthy weight reference population. Growth charts are useful and acceptable tools that professionals commonly use to improve counseling and facilitate behavior change (30). Therefore, these charts should be shown to parents before children develop obesity, to assist early prevention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there have been few studies primarily exploring the effect of intervention on perception of nutritional status among children or parents to date [ 15 , 16 , 17 ]. A randomized controlled trial in the USA assessed the effect of an educational intervention and revealed that parental perception of their children’s nutritional status was not improved [ 15 ]. Future work is necessary to elucidate the key factors affecting the accuracy of parental perception.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of observational or intervention types were focused on parental perception of their children’s nutritional status [ 12 , 13 , 14 , 15 ]. Our study is novel in its additional focus on students’ perception of their own nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation